Microalgae application for resource recovery - Thiraviyam S/O Pandian (Nanyang Technological University, 2023)
This report is centered on the operational performance of a photobioreactor holding a mixed co-culture system of microalgae and methanotrophic bacteria. Over a period of two semesters, various parameters relating to the operational performance of the photobioreactor, namely carbon consumption, the ammonium concentration of the system effluent, the Total Suspended Solids (TSS) and Volatile Suspended Solids (VSS) of the system’s biomass, were studied. Additionally, the dominant species of microalgae and methanotrophs in the inoculum were identified through DNA extraction and analysis. The intracellular constituents of the biomass were also deduced to explore the feasibility of useful products, such as the pre-cursor to aquaculture feed, being formed from this co-culture system, which could be scaled up for industrial biomass production in the future. A comparison was then drawn with existing fish, chicken and other protein meals, concluding the report.